Hydrophysical Database for Brazilian Soils (HYBRAS) and Pedotransfer Functions for Water Retention - Ottoni, M.V. (2020)
Data present in HYBRAS comprise 445 soil profiles with 1075 samples and are representative of a wide range of Brazilian soils. The data are organized in a relational structure of tables that cover general site descriptions, land cover, and hydrophysical and chemical measurement methods. Raw data (e.g., water retention points covering the 0–15,000‐cm suction range) and derived data are included in the tables. Another objective of this study was to use the database to compare the accuracy of water retention estimates based on PTFs developed for Brazilian and temperate regions. In general, the Brazilian PTFs performed better than the temperate models, especially for weathered (Ferralsols, Acrisols, and Nitisols) fine‐textured (clay, sandy clay, clay loam, silty clay loam, and silty clay) soils. Silt content was not a successful criterion for distinguishing performance of Brazilian and temperate PTFs for Brazilian weathered soils. The water retention of weathered soils was shown to differ from that of temperate soils due to differences in pore structure resulting from their clay content and mineralogical nature, thus confirming results reported in the literature.